Correlation between Elevated Serum Progesterone in the Day of Hcg Injection, Metaphase II Oocytes and Their Impact on The Success of ICSI - Ibrahim Badr, Hesham Sayed1 , Yahia Mohammed2 , Ahmed Mohamed2 , Mohammed Shehata3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: In this study we tried to understand the effect of progesterone level at the time of ovulationtrigger on intracytoplasmic sperm injection (ICSI) outcome. We expected identifying cut off values forserum progesterone level the day of hCG injection (P-hCG) & P-hCG per mature oocyte ratio (P-hCG /MII), as predictive tests of ICSI success. Methods: 200 women 18-40 years old and attending IVF unitof Kasr el Aini hospital for management of infertility were included in the study. They were scheduled forICSI after controlled ovarian induction with GnRH- agonist protocol. Inclusion criteria were tubal factorof infertility, unexplained infertility, polycystic ovarian syndrome and BMI ? 30 kg/m2. Exclusion criteriawere severe male factor infertility, hyperprolactinemic patients, high basal FSH > 11 IU/L, frozen embryotransfer cycles, uterine anomalies or synechia. Primary outcome parameter included correlation of serumprogesterone on day HCG administration, number of MII oocytes and calculated progesterone/ MII oocyteratio with success of ICSI.Results: 193cases underwent embryo transfer, 7cases cancelled. Clinical pregnancy was reported in 52(27.9%) cases. Higher P-hCG was observed in cases who didn’t get pregnant compared to those who gotpregnant (p= 0.01) with cut off value of 1 ng/ml correlated well with the clinical pregnancy rate after ICSIwith 61% sensitivity and 59% specificity (p=0.004). A significantly lower P-hCG/MII ratio was found inthe pregnant women group compared to that found in the non-pregnant group (p=0.001) and cut off valueof 0.18 correlated best with clinical pregnancy after ICSI with sensitivity 70.5% and specificity 61.2%(p<0.001). Conclusion : We demonstrated negative correlation between P-hCG and P-hCG/MII andclinical pregnancy rate after ICSI.